COMPARISON AND PHYLOGENETIC ANALYSIS OF THE CHLOROPLAST GENOMES OF SABINA PRZEWALSKII F. PENDULA AND JUNIPERUS PRZEWALSKII - Shuai-Peng Si; Ji-Zhong Wan; Ling-Hua Yang; Ze-Zhu Wu; Biao Xiong; Chun-Hui Zhang; Le Wang; Chun-Jing Wang (Journal of Animal and Plant Sciences, 2023)
Most species of the family Cupressaceae are widely distributed throughout China, but Sabina przewalskii f. pendula and Juniperus przewalskii are endemic to the Qinghai-Tibet Plateau region. Therefore, they are of great significance to the plateau ecosystem. Sabina przewalskii and J. przewalskii have similar characteristics, but they be distinguished by the presence or absence of drooping branchlets. However, this feature can be difficult to distinguish with the naked eye. In this study, the complete chloroplast (CP) genomes of S. przewalskii and J. przewalskii were determined by high-throughput sequencing, aiming to unveil their differences at the molecular level. The sizes of the CP genomes ofJ. przewalskii and S. przewalskii are 128,748 bp and 127,315 bp, respectively, sharing the typical structure of conifer species. The GC content of the S. przewalskii plastome is 35.08%, encoding 84 proteins, 32 tRNAs and 4 rRNAs. The GC content of the J. przewalskii CP genome is 34.98%, and one additional rpl32 gene was detected. Phylogenetic analysis proved that J. przewalskii showed a close relationship to Juniperus tibetica and S. przewalskii, both of which belong to the family Cupressaceae. Our results of the plastome of J. przewalskii and S. przewalskii further clarify the evolution of Cupressaceae species. The divergent regions and the repetitive sequences identified could be developed as molecular markers that would benefit breeding and species discrimination.
Keywords: Chloroplast genomes; Cupressaceae; Juniperus przewalskii; Sabina przewalskii f. pendula; Phylogenetic analysis